Graphene slurry as well as preparation method and application thereof
By combining graphene sheets with different specific surface areas and controlling homogeneous dispersion methods, the viscosity and particle size of graphene slurry are adjusted, and the problem of graphene slurry settlement is solved, and the appropriate viscosity and fluidity used in batteries are achieved.
Patent Information
- Application Number
- CN202411912162.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
Graphene slurry is prone to settle during actual storage and application, affecting its utilization in battery production.
By combining graphene sheets with different specific surface areas and combining high-voltage and low-voltage homogeneous dispersion methods, the viscosity and particle size of graphene slurry are regulated, the van der Waals attraction between graphenes is enhanced and the repulsion of electric double layer is reduced, and the settlement problem is improved.
The prepared graphene slurry takes into account both viscosity stability and fluidity. The normal viscosity is 200-2000 mPa.s, which is not easy to settle and is suitable for use as a conductive agent in batteries.
Smart Images

Figure CN119811746A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of conductive slurries, and in particular relates to a graphene slurry and a preparation method and application thereof. Background Art
[0002] Graphene is a new type of carbon nanomaterial, which is composed of a single layer of sp2 carbon atoms stacked into a two-dimensional honeycomb structure, and has excellent thermal conductivity and mechanical properties. Based on its "extremely thin and flexible" structural characteristics, graphene can form an effective conductive network in the active material particles through the "surface-point" contact mode, thereby improving battery performance. Therefore, graphene slurry is very suitable for use as a conductive agent in the battery field, especially in small particle material systems. However, graphene slurry is prone to sedimentation during actual storage and application, which is not conducive to its use in battery production. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a graphene slurry and a preparation method and application thereof, wherein the graphene slurry has both viscosity stability and fluidity and is not prone to sedimentation.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a graphene slurry, which comprises, by weight percentage, 1 to 10% of graphene, 0.1 to 4% of a dispersant and a balance of solvent;
[0006] The particle size D50 of the graphene is 2 to 8 μm; the viscosity of the graphene slurry is 200 to 2000 mPa.s.
[0007] Preferably, the solid content of the graphene slurry after standing for 30 days is 4±0.01%.
[0008] Preferably, the dispersant is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sodium lauryl sulfate and cetyltrimethylammonium bromide.
[0009] Preferably, the solvent is water or N-methylpyrrolidone.
[0010] The present invention also provides a method for preparing the graphene slurry described in the above technical solution, comprising the following steps:
[0011] Premixing the graphene sheets, the dispersant and the solvent, and sequentially performing sand milling dispersion and homogenization dispersion on the obtained mixed liquid to obtain the graphene slurry;
[0012] The graphene sheet includes a first graphene sheet and a second graphene sheet;
[0013] The specific surface area of the first graphene sheet is 100 to 300 m 2 / g; the specific surface area of the second graphene sheet is ≥30m 2 / g and <100m 2 / g;
[0014] The mass ratio of the first graphene sheet to the second graphene sheet is 20-40:60-80;
[0015] The homogeneous dispersion includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion performed sequentially.
[0016] Preferably, the number of layers of the first graphene sheet is 1 to 20; the number of layers of the second graphene sheet is 1 to 100; and the sheet diameters D50 of the first graphene sheet and the second graphene sheet are independently 10 to 100 μm.
[0017] Preferably, the sand milling dispersion time is 2 to 3 hours; the sand milling dispersion speed is 2000 to 4000 rpm.
[0018] Preferably, the shear rate during the homogeneous dispersion process is 50 to 70 / s.
[0019] Preferably, the pressure of the high-pressure homogenization dispersion is 40-60 MPa; the time of the high-pressure homogenization dispersion is 2-3 hours; the temperature of the high-pressure homogenization dispersion is 40-60° C.;
[0020] The pressure of the low-pressure homogeneous dispersion is ≥20MPa and <40MPa; the time of the low-pressure homogeneous dispersion is 1 to 2 hours.
[0021] The present invention also provides the use of the graphene slurry described in the above technical solution or the graphene slurry prepared by the preparation method described in the above technical solution as a conductive agent in a battery.
[0022] The present invention provides a graphene slurry, which comprises 1-10% of graphene, 0.1-4% of dispersant and the remainder of solvent in terms of mass percentage; the particle size D50 of the graphene is 2-8 μm; and the viscosity of the graphene slurry is 200-2000 mPa.s. The graphene slurry provided by the present invention has a small particle size of graphene, and the gravity on the graphene is smaller than the attraction between the graphenes, so that the graphene slurry is not easy to settle. The viscosity of the graphene slurry is appropriate, and while enhancing the viscosity stability and not easy to settle, it maintains good fluidity, which is conducive to use in batteries.
[0023] The present invention also provides a method for preparing the above-mentioned graphene slurry. The present invention can enhance the van der Waals attraction between graphene and reduce the double electric layer repulsion during the dispersion process by compounding graphene sheets with different specific surface areas, combined with controlling the homogeneous dispersion method (dispersion pressure and temperature), and then regulate the viscosity of the graphene slurry, and improve the sedimentation problem of the graphene slurry. First, the compounding of graphene with different specific surface areas can enhance the van der Waals attraction between graphene, can resist the effect of partial gravity, and reduce sedimentation; secondly, the homogeneous dispersion of the present invention includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion, and the high-pressure homogeneous dispersion process controls the temperature, can reduce the double electric layer repulsion between graphene, and enhance the attraction between graphene. At the same time, the large-particle-size graphene retained after high-pressure dispersion can be further dispersed and reduced under low-pressure homogeneous dispersion, and the small-particle-size graphene after high-pressure dispersion will not be further reduced under low-pressure homogeneous dispersion, which can increase the uniformity of the overall particle size of graphene. The graphene slurry prepared by the above method can balance viscosity stability and fluidity, and has no obvious sedimentation problem, making it conducive to use in batteries. At the same time, the method is simple, easy to operate, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the preparation method of graphene slurry in an embodiment of the present invention;
[0025] Figure 2 This is a physical picture of the graphene slurry prepared in Comparative Example 1 and Example 1 after standing for 30 days. DETAILED DESCRIPTION
[0026] The present invention provides a graphene slurry, which comprises, by weight percentage, 1 to 10% of graphene, 0.1 to 4% of a dispersant and a balance of solvent;
[0027] The particle size D50 of the graphene is 2 to 8 μm; the viscosity of the graphene slurry is 200 to 2000 mPa.s.
[0028] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0029] The graphene slurry provided by the present invention comprises graphene with a mass percentage of 1 to 10%, and in specific embodiments it can be 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%.
[0030] The mass percentage of graphene will affect the viscosity of the final graphene slurry. If the mass percentage is too high, the viscosity of the graphene slurry will be too high, causing the subsequent dispersion equipment to be unable to operate.
[0031] As an embodiment, the particle size D50 of the graphene is 2-8 μm, and in a specific embodiment, it is 5-7.5 μm. The graphene slurry provided by the present invention has a small particle size of graphene, and the gravity on the graphene is smaller than the attraction between the graphenes, so that the graphene slurry is not easy to settle.
[0032] The graphene slurry provided by the present invention comprises a dispersant with a mass percentage of 0.1 to 4%, and in a specific embodiment, 0.5 to 1%.
[0033] As an embodiment, the dispersant is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecyl sulfate and cetyltrimethylammonium bromide, and in a specific embodiment, it is polyvinyl pyrrolidone and polyvinyl alcohol; the mass ratio of polyvinyl pyrrolidone and polyvinyl alcohol is 20-80:20-80, and in a specific embodiment, it is 70:30.
[0034] The dosage of the dispersant affects the dispersion efficiency of the graphene slurry. Within the above dosage range of the dispersant, the graphene in the graphene slurry can be evenly dispersed and sedimentation can be reduced.
[0035] The graphene slurry provided by the present invention comprises a residual solvent.
[0036] As an embodiment, the solvent is water or N-methylpyrrolidone, and in a specific embodiment, it is N-methylpyrrolidone.
[0037] As an embodiment, the viscosity of the graphene slurry is 200-2000 mPa.s, and in specific embodiments, it is 209 mPa.s, 468 mPa.s or 1558 mPa.s; the solid content of the graphene slurry after standing for 30 days is 4±0.01%, and in specific embodiments, it is 4%.
[0038] The present invention also provides a method for preparing the graphene slurry described in the above technical solution, comprising the following steps:
[0039] Premixing the graphene sheets, the dispersant and the solvent, and sequentially performing sand milling dispersion and homogenization dispersion on the obtained mixed liquid to obtain the graphene slurry;
[0040] The graphene sheet includes a first graphene sheet and a second graphene sheet;
[0041] The specific surface area of the first graphene sheet is 100 to 300 m 2 / g; the specific surface area of the second graphene sheet is ≥30m 2 / g and <100m 2 / g;
[0042] The mass ratio of the first graphene sheet to the second graphene sheet is 20-40:60-80;
[0043] The homogeneous dispersion includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion performed sequentially.
[0044] The present invention premixes graphene sheets, a dispersant and a solvent to obtain a mixed liquid.
[0045] As an embodiment, the graphene sheet includes a first graphene sheet and a second graphene sheet; the specific surface area of the first graphene sheet is 100 to 300 m 2 / g, in the specific embodiment, 150-250m 2 / g; the specific surface area of the second graphene sheet is ≥30m 2 / g and <100m 2 / g, in the specific embodiment, 40 to 60 m 2 / g; the mass ratio of the first graphene sheet to the second graphene sheet is 20-40:60-80, and in a specific embodiment is 40:60.
[0046] As an implementation manner, the number of layers of the first graphene sheet is 1 to 20 layers, and in a specific embodiment, it is 12 to 15 layers; the number of layers of the second graphene sheet is 1 to 100 layers, and in a specific embodiment, it is 50 to 70 layers.
[0047] As an implementation manner, the sheet diameter D50 of the first graphene sheet and the second graphene sheet is independently 10 to 100 μm, and in a specific embodiment, 30 to 90 μm.
[0048] Gravity acts as a repulsive force, and the force brought by the specific surface area acts as an attractive force. The larger the diameter of the graphene sheet, the greater its own gravity in the graphene slurry, and the easier it is to settle. The fewer the graphene layers, the larger the specific surface area, and the greater the attractive force brought by the surface force, which will offset the effect of gravity, increase the viscosity of the graphene slurry, and reduce sedimentation.
[0049] As an embodiment, the premixing is: first, the dispersant and the solvent are mixed and stirred for a first time to obtain a premixed solution; the graphene sheets are added to the premixed solution, and stirred for a second time to obtain a mixed liquid; the rotation speed of the first stirring is 600 to 1000 rpm, and in a specific embodiment, it is 700 to 900 rpm; the time of the first stirring is 0.5 to 1 h, and in a specific embodiment, it is 0.5 h; the rotation speed of the second stirring is 600 to 1000 rpm, and in a specific embodiment, it is 700 to 900 rpm; the time of the second stirring is 0.5 to 1 h, and in a specific embodiment, it is 0.5 h.
[0050] After obtaining the mixed liquid, the present invention sequentially performs sand milling dispersion and homogenization dispersion on the mixed liquid to obtain the graphene slurry.
[0051] As an implementation mode, the sand milling dispersion time is 2 to 3 hours, and in a specific embodiment, it is 2 to 2.5 hours; the equipment used for the sand milling dispersion is a sand mill; the grinding balls used for the sand milling dispersion are zirconium balls; the ball diameter of the grinding balls used for the sand milling dispersion is 0.5 to 2.0 mm, and in a specific embodiment, it is 1 to 1.5 mm; the rotation speed of the sand milling dispersion is 2000 to 4000 rpm, and in a specific embodiment, it is 2500 to 3500 rpm.
[0052] As an implementation mode, the particle size D50 of the graphene in the mixed liquid after sand milling dispersion is 10 to 20 μm, and in a specific embodiment is 15 to 18 μm.
[0053] As an embodiment, the homogeneous dispersion includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion performed in sequence; the pressure of the high-pressure homogeneous dispersion is 40-60MPa, and in a specific embodiment, it is 50-60MPa; the time of the high-pressure homogeneous dispersion is 2-3h, and in a specific embodiment, it is 2.5h; the temperature of the high-pressure homogeneous dispersion is 40-60°C, and in a specific embodiment, it is 40-50°C; the pressure of the low-pressure homogeneous dispersion is ≥20MPa and <40MPa, and in a specific embodiment, it is 20-30MPa; the time of the low-pressure homogeneous dispersion is 1-2h, and in a specific embodiment, it is 1h.
[0054] As an implementation mode, the shear rate during the homogeneous dispersion process is 50 to 70 / s, and in a specific embodiment, it is 40 to 60 / s.
[0055] Homogeneous dispersion in the present invention includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion. The dispersion pressure of high-pressure homogeneous dispersion is large, the dispersion strength is large, and the graphene particle size decreases quickly. The dispersion pressure of low-pressure homogeneous dispersion is small, and the dispersion strength is small. The large-particle graphene that is not fully dispersed by high-pressure homogeneous dispersion can be further dispersed and reduced, and the small-particle graphene will not be further reduced under low-pressure homogeneous dispersion, which can increase the uniformity of the overall particle size of the graphene. In the high-pressure homogeneous dispersion process, due to the large dispersion pressure, the temperature rises, and the temperature is too high, which will cause the viscosity of the graphene slurry to change suddenly, so it is necessary to control the temperature in the high-pressure homogeneous dispersion process within the above range.
[0056] The DLVO theory divides the interaction force between graphene in solution into van der Waals attraction (ΦVDW) and double electric layer repulsion (ΦEDL). The stability of graphene slurry depends on the relative magnitude of the two opposing forces, van der Waals attraction and double electric layer repulsion. These two potential energies per unit area can be expressed by formulas (1) and (2) respectively. The increase in temperature will have a significant effect on γ i =tand(veψ i / 4kT) and (kT / ve) 2 has the opposite effect, and γi =tand(veψ i / 4kT) plays a major role. Within a certain range, the increase in temperature will reduce the double-layer repulsion, and the van der Waals attraction of graphene is greater than the double-layer repulsion, which in turn causes the graphene viscosity to increase. The present invention can enhance the van der Waals attraction between graphenes by compounding graphene sheets with different specific surface areas, and control the temperature and the particle size of the graphene slurry by high-pressure homogenization and dispersion, thereby enhancing the van der Waals attraction between graphenes and reducing the double-layer repulsion during the dispersion process, and then regulating the viscosity of the graphene slurry, so that it takes into account both viscosity stability and fluidity, and the normal viscosity is 200-2000mPa.s, which is not easy to produce sedimentation.
[0057] Φ VDW =-A / (12πd 2 ) (1)
[0058] Φ EDL =32ε 0 ε T κγ 1 γ 2 kT / ve) 2 exp(-κd) (2)
[0059] Where d is the interlayer distance between two graphene sheets, A is the Hamaker constant; γ i =tand(veψ i / 4kT)(i=1,2),ε 0 is the dielectric constant of vacuum, ε T is the relative dielectric constant of the solution, ψ i is the surface potential, usually approximated by the zeta potential, κ is the Debye-Hückel constant, v is the ionic strength of the electrolyte, e is the electron charge, k is the Boltzmann constant, and T is the absolute temperature.
[0060] Figure 1 FIG. 1 is a schematic diagram of a method for preparing a graphene slurry according to an embodiment of the present invention. Figure 1 As shown, the present invention obtains a first graphene sheet, a second graphene sheet, a dispersant and a solvent, premixes the dispersant and the solvent, then adds the first graphene sheet and the second graphene sheet to the obtained premixed solution for sand milling and dispersion, and finally homogenously disperses the sand milled slurry to obtain a graphene slurry.
[0061] The graphene slurry prepared by the present invention takes into account both viscosity stability and fluidity, has a normal viscosity of 200 to 2000 mPa.s, and is not prone to sedimentation.
[0062] The present invention also provides the use of the graphene slurry described in the above technical solution or the graphene slurry prepared by the preparation method described in the above technical solution as a conductive agent in a battery.
[0063] The present invention has no special limitation on the application of the graphene slurry as a conductive agent in a battery, and any application method known in the art may be used.
[0064] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0065] Example 1
[0066] Taking the total weight of the graphene slurry as 100%, the raw materials for preparing the graphene slurry include 3% by weight of graphene sheets, 1% by weight of a dispersant (polyvinyl pyrrolidone and polyvinyl alcohol in a mass ratio of 70:30), and the remainder is N-methylpyrrolidone;
[0067] The graphene sheet is composed of a first graphene sheet and a second graphene sheet with a mass ratio of 40:60, wherein the sheet diameter D50 of the first graphene sheet is 30.5 μm, the main number of layers is 12 to 15 layers of horizontally arranged graphene sheets, and the specific surface area is 218 m 2 / g; the second graphene sheet has a sheet diameter of D50 = 90 μm, and the main number of layers is 50 to 70 layers of horizontally arranged graphene sheets, with a specific surface area of 51m 2 / g;
[0068] The preparation method of graphene slurry is as follows:
[0069] Polyvinyl pyrrolidone and polyvinyl alcohol were mixed with N-methyl pyrrolidone, and stirred at 900 rpm for 0.5 h to obtain a premixed solution, and graphene sheets were added to the premixed solution, and stirred at 900 rpm for 0.5 h. The obtained mixed liquid was transferred to a sand mill for sand grinding and dispersion, and ground with 1 mm zirconium beads at a speed of 2500 rpm for 2 h to obtain a mixed liquid after sand grinding and dispersion with a graphene particle size D50 = 17.5 μm;
[0070] The mixed liquid after sand grinding and dispersion was transferred to a high-pressure homogenizer for homogenization and dispersion for 3.5 hours, firstly high-pressure homogenization and dispersion was carried out at 50 MPa for 2.5 hours, the temperature was controlled at 40°C, and then low-pressure homogenization and dispersion was carried out at 30 MPa for 1 hour. The shear rate during the homogenization and dispersion process was 50 / s, and finally a graphene slurry with a graphene particle size of D50=6.1 μm and a viscosity of 209 mPa.s was obtained.
[0071] Examples 2 to 3 and Comparative Examples 1 to 11
[0072] The differences from Example 1 are shown in Table 1, and the rest of the contents are consistent with Example 1.
[0073] Table 1 Conditions of Examples 2 to 3 and Comparative Examples 1 to 11
[0074]
[0075] Performance Testing
[0076] (1) The viscosity and solid content of the graphene slurries of Comparative Examples 1 to 6 are shown in Table 2.
[0077] Table 2 Viscosity and solid content of graphene slurry of comparative examples 1 to 6
[0078]
[0079] As shown in Table 2, the viscosity and solid content of the graphene slurry prepared by the ratio of graphene sheets with different specific surface areas, the 30-day static viscosity results show that as the proportion of the first graphene increases, the initial viscosity also increases. When the first graphene ratio increases to more than 40%, the initial viscosity of the graphene slurry increases slightly. In addition, from the results of the solid content change, it can be seen that as the initial viscosity increases, the downward trend of the solid content decreases significantly, indicating that the viscosity increase can significantly improve the sedimentation of the graphene slurry. Graphene sheets with different high specific surface area ratios can increase the initial slurry viscosity and have a certain improvement on sedimentation, but the improvement effect is limited.
[0080] (2) The viscosity and solid content of the graphene slurries of Examples 1 to 3 and Comparative Examples 1 and 7 are shown in Table 3.
[0081] Table 3 Viscosity and solid content of graphene slurries of Examples 1 to 3 and Comparative Examples 1 and 7
[0082]
[0083] As shown in Table 3, by verifying the influence of different high-pressure homogenization dispersion temperatures, the graphene slurries prepared in Examples 1 to 3 have good fluidity, and the solid content has not decreased significantly after 30 days of static standing; while the graphene slurry prepared in Comparative Example 7 (70°C) has a large initial viscosity (>2000mPa.s), and the fluidity may be affected, which is not conducive to the use of downstream battery factories. From the above results, it can be seen that the initial viscosity of the graphene slurry can be controlled by appropriate temperature control within 40 to 60°C. When the temperature is too high (≥70°C), the viscosity will suddenly change, affecting the basic properties of the graphene slurry.
[0084] (3) The viscosity and solid content of the graphene slurries of Comparative Examples 8 to 11 are shown in Table 4.
[0085] Table 4 Viscosity and solid content of graphene slurry of comparative examples 8 to 11
[0086]
[0087] As shown in Table 4, the influence of graphene particle size was obtained by verifying different dispersion times. The above results show that when D50 is less than 2 μm, the slurry viscosity is less affected under stable conditions, but the dispersion time is significantly increased, affecting the dispersion efficiency. When D50 is greater than 8 μm, the slurry viscosity stability deteriorates. The possible reason is that the graphene particle size is larger, and the gravity on the graphene is greater than the attraction between the graphene particles, resulting in the sedimentation of the graphene, which leads to a decrease in the graphene content in the upper layer of the slurry and a decrease in the solid content.
[0088] The above verification results show that the present invention can prepare graphene slurry with suitable viscosity by regulating the ratio of graphene sheets with different specific surface areas, the temperature of high-pressure homogeneous dispersion, and the graphene particle size in the graphene slurry, which can significantly improve the sedimentation problem of the graphene slurry.
[0089] (4) Figure 2 This is a physical picture of the graphene slurry prepared in Comparative Example 1 and Example 1 after standing for 30 days.
[0090] from Figure 2 It can be seen that the graphene slurry prepared in Comparative Example 1 has obvious sedimentation after standing for 30 days, while the graphene slurry prepared in Example 1 has no obvious sedimentation after standing for 30 days.
[0091] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A graphene slurry, characterized in that: Calculated by mass percentage, it includes 1-10% of graphene, 0.1-4% of dispersant and the balance of solvent; The particle size D50 of the graphene is 2 to 8 μm; the viscosity of the graphene slurry is 200 to 2000 mPa.s.
2. The graphene slurry according to claim 1, characterized in that: The solid content of the graphene slurry after standing for 30 days is 4±0.01%.
3. The graphene slurry according to claim 1, characterized in that: The dispersant is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sodium lauryl sulfate and cetyltrimethylammonium bromide.
4. The graphene slurry according to claim 1, characterized in that: The solvent is water or N-methylpyrrolidone.
5. The method for preparing the graphene slurry according to any one of claims 1 to 4, characterized in that: The following steps are involved: Premixing the graphene sheets, the dispersant and the solvent, and sequentially performing sand milling dispersion and homogenization dispersion on the obtained mixed liquid to obtain the graphene slurry; The graphene sheet includes a first graphene sheet and a second graphene sheet; The specific surface area of the first graphene sheet is 100 to 300 m 2 / g; the specific surface area of the second graphene sheet is ≥30m 2 / g and <100m 2 / g; The mass ratio of the first graphene sheet to the second graphene sheet is 20-40:60-80; The homogeneous dispersion includes high-pressure homogeneous dispersion and low-pressure homogeneous dispersion performed sequentially.
6. The preparation method according to claim 5, characterized in that: The number of layers of the first graphene sheet is 1 to 20; the number of layers of the second graphene sheet is 1 to 100; and the sheet diameters D50 of the first graphene sheet and the second graphene sheet are independently 10 to 100 μm.
7. The preparation method according to claim 5, characterized in that: The sand milling dispersion time is 2 to 3 hours; the sand milling dispersion speed is 2000 to 4000 rpm.
8. The preparation method according to claim 5, characterized in that: The shear rate during the homogeneous dispersion process is 50 to 70 / s.
9. The preparation method according to claim 5 or 8, characterized in that: The pressure of the high-pressure homogenization dispersion is 40-60 MPa; the time of the high-pressure homogenization dispersion is 2-3 hours; the temperature of the high-pressure homogenization dispersion is 40-60°C; The pressure of the low-pressure homogeneous dispersion is ≥20MPa and <40MPa; the time of the low-pressure homogeneous dispersion is 1 to 2 hours.
10. Use of the graphene slurry according to any one of claims 1 to 4 or the graphene slurry prepared by the preparation method according to any one of claims 5 to 9 as a conductive agent in a battery.